Unraveling signatures of chicken genetic diversity and divergent selection in breed-specific patterns of early myogenesis, nitric oxide metabolism and post-hatch growth - Kochish, Ivan I.; Titov, Vladimir Yu.; Nikonov, Ilya N.; Brazhnik, Evgeni A.; Vorobyov, Nikolai I.; Korenyuga, Maxim V.; Myasnikova, Olga V.; Dolgorukova, Anna M.; Griffin, Darren K.; Romanov, Michael N. (Frontiers in Genetics, 2023)
Due to long-term domestication, breeding and divergent selection, a vast genetic diversity in poultry currently exists, with various breeds being characterized by unique phenotypic and genetic features. Assuming that differences between chicken breeds divergently selected for economically and culturally important traits manifest as early as possible in development and growth stages, we aimed to explore breed-specific patterns and interrelations of embryo myogenesis, nitric oxide (NO) metabolism and post-hatch growth rate (GR). These characteristics were explored in eight breeds of different utility types (meat-type, dual purpose, egg-type, game, and fancy) by incubating 70 fertile eggs per breed. To screen the differential expression of seven key myogenesis associated genes (MSTN, GHR, MEF2C, MYOD1, MYOG, MYH1, and MYF5), quantitative real-time PCR was used. We found that myogenesis associated genes expressed in the breast and thigh muscles in a coordinated manner showing breed specificity as a genetic diversity signature among the breeds studied. Notably, coordinated (“accord”) expression patterns of MSTN, GHR, and MEFC2 were observed both in the breast and thigh muscles. Also, associated expression vectors were identified for MYOG and MYOD1 in the breast muscles and for MYOG and MYF5 genes in the thigh muscles. Indices of NO oxidation and post-hatch growth were generally concordant with utility types of breeds, with meat-types breeds demonstrating higher NO oxidation levels and greater GR values as compared to egg-type, dual purpose, game and fancy breeds. The results of this study suggest that differences in early myogenesis, NO metabolism and post-hatch growth are breed-specific; they appropriately reflect genetic diversity and accurately capture the evolutionary history of divergently selected chicken breeds.